The backpacker's handbook / Chris Townsend - Townsend, Chris
A guide to equipment and technique which includes information on techniques such as map and compass work and the skills needed for more remote wilderness journeys - such as how to ford rivers safely and how to choose a route through untracked terrain. It also covers desert hiking, ultralight backpacking, and adventure trekking.